Polityka wewnętrzna Karola Ludwika Bonapartego w latach 1848-1852 w ocenie historyków polskich ........ 167 - Król, Damian (Od Sumeru do zimnej wojny, 2025)
THE INTERNAL POLICY OF CHARLES LOUIS BONAPARTE IN THE YEARS 1848-1852 IN THE ASSESSMENT OF POLISH HISTORIANSThe article provides an in-depth analysis of the approach of Polish historians to the internal politics of Charles Louis Bonaparte, starting from his entry into the political scene as a deputy to the Assembly and ending with the coup d’état of 1851. The research is based on works from the 19th and 20th centuries. It includes studies published both during the reign of President, and later Emperor, Napoleon III, as well as after their conclusion. Polish historiography has so far lacked a comprehensive view on issues related to Napoleon III’s internal politics, which led me to conduct this detailed analysis. Existing works touched only on selected aspects of the issue, and none were dedicated to this subject in its entirety. The most valuable work in which this topic was addressed remains the biography of Napoleon III by Alfred Liebfeld, published in the late 1970s. The main goal of the article is to trace the changing attitude of Polish historians towards the actions of the deputy and president in the context of internal politics. The analysis will cover different periods of time, showing the evolution of historians’ perspectives on Charles Louis’s politics. It will also examine trends present in historians’ interpretations, highlighting which aspects of internal politics were considered important and which were overlooked. Based on the aforementioned research works, the article will focus on answering questions about how Polish historians evaluated particular aspects of Charles Louis Bonaparte’s internal politics in various periods, whether there were changes in their perceptions, and what factors influenced the evolution of this perspective. This analysis will contribute to a better understanding of the emperor’s impact on 19th-century France from the perspective of Polish historiography.